Does the gender-equality paradox hold on the micro level? An assessment of the effect of household wealth on gendered math intentions for 60 countries - Uunk, Wilfred (Frontiers in Education, 2023)
The Gender-Equality Paradox (GEP) describes the phenomenon that the gender gap in the preference for and choice of science, technology, engineering, and mathematics (STEM) majors is larger in more affluent and gender-egalitarian societies. GEP has theoretically been explained by greater economic opportunities in affluent societies for gendered self-realization, yet the literature lacks a test of this explanation on the individual level. This study tests (a) whether household wealth is associated with a greater male-favorable gender gap in student’s math intentions, (b) whether this association, if any, is different in size and shape in more affluent and less affluent countries, and (c) whether household wealth can account for GEP regarding math intentions. Multilevel regression analyses of 15-year-old students’ intentions to study math rather than language from 60 countries of the Programme for International Student Assessment (PISA) 2012 display that household wealth is only weakly and positively related to girls’ and boys’ math intentions and does not in- or decrease the gender gap in math intentions. This pattern of household wealth effects does not differ between more affluent and less affluent countries, and household wealth cannot account for GEP regarding math intentions. These findings underline that the economic need/opportunity interpretation of GEP does not hold on the micro level and require further research into the drivers of GEP.